Biocompatible nanoparticles self-assembled by PEGylated polyphosphoesters for combination of photodynamic therapy and hypoxia-activated chemotherapy against breast cancer - Wang, Fengyu; Zou, Xiaojing; Sun, Chunyang (Frontiers in Pharmacology, 2024)
IntroductionAlthough photodynamic therapy (PDT) shows considerable potential for cancer treatment due to its precise spatial control and reduced toxicity, effectively eliminating residual cells under hypoxic conditions remains challenging because of the resistance conferred by these cells.MethodsHerein, we synthesize an amphiphilic PEGylated polyphosphoester and present a nanocarrier (NPCT) specifically designed for the codelivery of hydrophobic photosensitizer (chlorin e6, Ce6) and hypoxia-activated prodrugs (tirapazamine, TPZ). We investigate the antitumor effect of NPCT on both cellular and animal level.ResultsThe efficient encapsulation of Ce6 and TPZ by NPCT enables the prolonged blood circulation and improved tumor distribution of both agents. Upon internalization by tumoral cells, 660 nm laser irradiation activates Ce6, leading to the generation of reactive oxygen species (ROS) that effectively kill murine 4T1 breast cancer cells. Meanwhile, the PDT process consumes a large amount of oxygen to generate the hypoxic microenvironment that activates the liberated TPZ from NPCT. The resulting highly cytotoxic radicals specifically target and induce cytotoxicity in remaining hypoxic cancer cells. Compared to other groups, the combination of NPCT and 660 nm laser irradiation resulted in the most substantial tumor growth inhibition.DiscussionThis innovative approach provides new avenues for the development of advanced delivery systems based on polyphosphoesters and combination therapeutic strategies.